Avaliação mecânica in vitro utilizando miniplacas quadradas e retangulares do sistema 2.0 mm em fraturas da região anterior de mandíbula - Oliveira, Kerlison Paulino de (2012)
The aim of this study was to comparatively evaluate the mechanical strength of squared and rectangular 2.0 mm system miniplates comparing them to the standard configuration with 2 straight miniplates in stabilizing fractures in the anterior mandible. Ninety synthetic polyurethane mandible replicas were used in mechanical test. The samples were divided into six groups of three different methods for fixation. Groups 1, 2 and 3 showed complete fractures in symphysis, characterized by a linear separation between the medial incisor, and groups 4, 5 and 6 showed complete fractures in parasymphysis with oblique design. Groups 1 and 4 were represented by the standard technique with two straight miniplates parallel to each other. Groups 2 and 5 were stabilized by squared miniplates and groups 3 and 6 were fixed by rectangular design. Each group was subjected to a mechanical test at a displacement speed of 10 mm/min on a universal testing machine, receiving linear vertical load on the region of the left first molar. The values of the maximum load and when displacements reached 5 mm were obtained and statistically analyzed by calculating the confidence interval of 95%. Fixation systems using squared (G2) and rectangular (G3) miniplates obtained similar results. No statistically significant differences with respect to the maximum load and the load at 5 mm displacement were found when compared to standard method in symphyseal fractures (G1). In parasymphysis the fixation method using squared miniplates (G5) obtained results without significant differences regarding the maximum load and the load at 5 mm when compared to the standard configuration (G4). The fixation method using rectangular miniplates (G6) showed inferior results which were statistically significant when compared to the standard configuration (G4) for parasymphysis fractures. The mechanical behavior of the fixation methods was similar, except when rectangular miniplates were used. The fixation methods showed better results with statistical significance in symphyseal fractures